Actual time determination of egg freshness: A centroid rate based approach. (December 2020) - Tan, Wen; Zhang, Qinjun; Yang, Lu; Tian, Liangjie; Jia, Jie; Lu, Mei; Liu, Xuebo; Duan, Xiang
Highlights: The centroid rate changed synchronously with egg freshness during storage. The egg yolk position continually changed with redistribution and diffusion of water. The centroid position of eggs directionally moved towards the blunt end. A rapid, actual-time approach to nondestructively determine egg freshness was reported. Abstract: Developing rapid and nondestructive technologies to evaluate egg quality is meaningful for both industrial and consumer application. In this work, a novel determination technology based on centroid rate was explored. Egg samples were stored at 25 °C and 50–60 % relative humidity. With increasing of storage time, the water states of eggs changed with an increase in immobilized water and a decrease in free water. The egg yolk continuously moved to the air chamber with redistribution and diffusion of water, causing the centroid position of eggs directionally to move towards the blunt end. Accordingly, the correlation between the centroid rate and Haugh unit (HU) value has been established, and the coefficient of determination (R 2 ) in the predictive model reached 0.961. This suggested that the approach possessed a high accuracy and had a potential to be applied in evaluating egg quality in actual time during storage.